2018
DOI: 10.1039/c8ra05728a
|View full text |Cite
|
Sign up to set email alerts
|

Structural modification of oridonin via DAST induced rearrangement

Abstract: A novel and concise synthetic approach for the preparation of 6,20-epoxy ent-kaurane diterpenoid from oridonin was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…The lack of selectivity between normal and cancer cells is one of the primary limitations of antitumor drugs [ 20 ]. We evaluated the cytotoxicity of compounds 4c , 4e – 4i , 4l , 4m , and 4q in the normal cell line L-02 to determine the selectivity index (defined as the ratio of cytotoxicity in L-02 cells compared to that in cancer cells).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of selectivity between normal and cancer cells is one of the primary limitations of antitumor drugs [ 20 ]. We evaluated the cytotoxicity of compounds 4c , 4e – 4i , 4l , 4m , and 4q in the normal cell line L-02 to determine the selectivity index (defined as the ratio of cytotoxicity in L-02 cells compared to that in cancer cells).…”
Section: Resultsmentioning
confidence: 99%
“…This opens a new way for development of anti-cancer agents. [73] Also in the syntheses of steroid derivatives, examples of rearrangements using DAST are known. Diethylaminosulfur trifluoride can induce carbocation formation, which then undergoes ring expansion.…”
Section: Debenzylative Cycloetherification In the Synthesis Of Sugars Derivativesmentioning
confidence: 99%
“…[72] Tang research group reported an efficient method for preparation of novel 6,20-epoxy ent-kaurane diterpenoid analogues 231 from oridonin, in which 6,20-endo ring was formed by DAST induced rearrangement (Scheme 50). [73] It is worth emphasizing that the incorporated functionalities R had a trivial impact on the transformation. When 228 was treated with DAST in the presence of (E)-3-(3,4-dimethoxyphenyl)acrylic acid (pathway b), the 1-acetyl-6,14-diacyl oridonin analogue 233 was obtained as the main product in 83 % yield.…”
Section: Fluorinated and Rearranged Terpenoids And Steroidsmentioning
confidence: 99%
“…The residue was subjected to column chromatography (silica gel, EtOAc/petroleum ether, 1:4) to give compound 15 (yield 41% from compound 11) as a white powder. 46 1 H NMR (300 MHz, CDCl 3 ): δ 6.11 (s, 1H), 5.49 (s, 1H), 4.56 (s, 1H), 4.17 (s, 1H), 3.96 (d, J = 9.2 Hz, 1H), 3.79 (d, J = 9.7 Hz, 2H), 3.10 (d, J = 8.0 Hz, 1H), 2.38 (tt, J = 8.5, 4.8 Hz, 1H), 2.00 (dd, J = 14.6, 7.0 Hz, 1H), 1.81 (d, J = 13.5 Hz, 1H), 1.71−1.61 (m, 3H), 1.61−1.47 (m, 4H), 1.24−1.12 (m, 2H), 1.00 (t, J = 5.4 Hz, 6H); 13 (3S,3aR,3a1R,6aR,7S,7aR,11S,11aS,11bS)-7-Hydroxy-5,5,8,8-tetramethyl-15-methylene-14-oxodecahydro-2H-6a,11a-(epoxymethano)-3,3a1-ethanophenanthro[1,10-de][1,3]dioxin-11-yl Methanesulfonate (16). Compound 16 was prepared as previously described for compound 11 in our prior work.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The residue was subjected to column chromatography (silica gel, EtOAc/petroleum ether, 1:10 to 1:6) to give compound 21 as a mixture of diastereoisomers with 2:1 dr (5.24 g, 21a/21b 2:1, 88% overall yield). 46 [1,3]dioxin-14-one (22). To a solution of the mixture of diastereoisomers of 21 (1.8 g, 3.2 mmol) in anhydrous toluene (30 mL) were added AIBN (203 mg, 1.2 mmol) and nBu 3 SnH (4.8 mL, 17.9 mmol).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%